Grief and bereavement in the adult palliative care setting - Strada, E. Alessandra (Oxford American palliative care library., 2013)
For patients and family caregivers the journey through illness and transitions of care is characterized by a series of progressive physical and emotional losses. Grief reactions represent the natural response to those losses. Grief is defined by a constellation of physical, cognitive, emotional and spiritual manifestations, varying in length and severity. While grief reactions are common and expected responses to loss, they have the potential to cause significant suffering. And, while grief is not a disease, it can develop into a pathological process warranting specialized treatment. Additiona.